THE ROLE OF THE CHIEF FINANCIAL OFFICER IN EXPLAINING THE DIFFERENCE BETWEEN THE APPLICATION OF ACCOUNTING STANDARD12 AND THE IRAQI LAW OF AL-ZARIFI TO ACHIEVE JUSTICE (World Bulletin of Social Sciences, 2022)
The research aims to clarify the importance of adopting IAS (12) "income taxes" as a tool for measuring and disclosing income taxes in financial statements by comparing the calculation of income tax according to the standard in question and the calculation of tax according to Iraqi accounting rule No. 13.
Keywords: consequences; discrepancy; focused